Small pelagic fish at the feed-food nexus in sub-Saharan Africa: a scoping review - Wesana, Joshua; Yossa, Rodrigue; Bunting, Stuart W.; Cohen, Philippa J. (Frontiers in Sustainable Food Systems, 2025)
IntroductionNourishing the growing and changing global population within sustainable limits is a pressing concern that must be addressed by 2030. To meet this challenge, it is argued food systems must transform, but a range of different food system configurations and trade-offs must be considered by national, regional and global decision-makers. Wild caught Small Pelagic Fish Species (SPFS) are a valuable source of human nutrition and are also frequently processed into fish meal and fish oil to become the principal protein and lipid sources for farmed animal feeds. The choices between the primary (i.e., for direct human consumption) and secondary (i.e., for animal feed ingredients) uses of small-pelagic freshwater and marine fish provides an illustrative example of contention and opportunity in balancing livelihood, income, consumer demand and human nutrition needs. Whilst the potential trade-offs have received much popular attention, there is a clear need to examine the evidence.MethodsIn this paper, we systematically collate peer reviewed literature and trade data from the African Great Lakes Region (AGLR) and the western coastal region of sub-Saharan Africa. A total of 201 articles met our search criteria, and of those we deemed 32 to hold sufficient and quality data for use in this review.ResultsThe AGLR (76%), and specifically Kenya (64%), were best represented in the literature which covered alternative feed proteins, assessment of feed/food nutritional quality and availability of feed/food resources. We find that the use of SPFS as feed limits access for use as food. This further supports innovations to develop fish oil and fish meal alternatives to safeguard SPFS for direct human consumption, particularly in resource-poor contexts.DiscussionSince most extracted evidence in this review was from the AGLR, there is still a need for more targeted investments for robust research that is cross-regional to better understand the magnitude, dynamics and trade-offs concerning the utilization of SPFS in SSA.